GAMBARAN SIKAP MASYARAKAT SAAT MELINTASI PERLINTASAN KERETA API TIDAK RESMI DI KOMPLEK BUMI LUBUK BUAYA INDAH (BLBI) KELURAHAN LUBUK BUAYA KECAMATAN KOTO TANGAH KOTA PADANG TAHUN 2019 - Haryani, Sesmeri; Hidayanti, Widya (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
Railway accident data from Padang Divre II in 2018 have recorded several accidents at the crossing that pass through Lubuk Buaya Sub-district precisely in front of the Bumi Lubuk Buaya Indah Complex (BLBI) like a motorcycle rider was hit by a train because the driver did not turn right or left before crossing a railroad crossing, a car that was hit by a train because the driver did not open the driver's side window when crossing a railroad crossing, and pedestrians were hit by a train that passed because the victim stood on the edge of the railroad. The purpose of this study was to determine the description of attitudes and attitude components (cognitive, affective, and conative) of the community when crossing an informal railroad crossing. The design of this research is descriptive quantitative. The research is located in the Bumi Lubuk Buaya Indah (BLBI) Complex, Lubuk Buaya Sub-District, Koto Tangah District, Padang City. This research was conducted in February-September 2019. The respondents of this study were 86 people and the selection of respondents was done by random sampling. The results of this study found that 11.6% of respondents had bad attitudes, 11.6% of respondents had poor cognitive, 9.5% of respondents had poor affective behavior, and 3.5% of respondents had poor conative behavior. It is expected that the community will instill and cultivate orderly and obey the rules when crossing a railroad crossing, form a railroad-loving community, appoint residents to guard the doorstop, and people who violate the crossing are given a fine.